The Influence of intellectual intelligence, spiritual intelligence, anf interest in reading on the love of understanding of financial management (Case study on students of management study program, faculty of Economics, Tamanasiswa Bachelor Wiyata University ) - Rinofah, Risal; Maulida, Alfiatul; Julaiha, Julaiha (Invoice : Jurnal Ilmu Akuntansi, 2023)
This study aims to examine the effect of intellectual intelligence, spiritual intelligence, and reading interest at the level of understanding of financial management. The sample in this study were students of the management study program, Faculty of Economics, Universitas Bachelor of Tamansiswa, based on the questionnaire method, 80 students were obtained. In this study, the data were processed using SPSS. The hypothesis testing method uses a significance level of 0.05 (5%). The results showed that the intellectual intelligence variable had an effect on the level of understanding of financial management. Spiritual intelligence variables affect the level of understanding of financial management. The variable of reading interest has an effect on the level of understanding of financial management